2020
DOI: 10.3389/fcimb.2020.565465
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein Receptor-Related Protein-1 (LRP1) Is Involved in the Uptake of Clostridioides difficile Toxin A and Serves as an Internalizing Receptor

Abstract: Toxin producing Clostridioides difficile strains cause gastrointestinal infections with the large glucosylating protein toxins A (TcdA) and B (TcdB) being major virulence factors responsible for the onset of symptoms. TcdA and TcdB enter their target cells via receptor-mediated endocytosis. Inside the cell, the toxins glucosylate and thereby inactivate small GTPases of the Rho-/Ras subfamilies resulting in actin reorganization and cell death. The receptors of TcdA are still elusive, glycoprotein 96 (gp96), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Recent studies showed that TcdA uses sulfated glycosaminoglycans as the cell surface attachment factors and LDLR family proteins as the entry receptors. 8 , 12 The primary sequences between Tcnα and TcdA are divergent, with only ~30% identity. In the LCT family, TcdA is most similar to TcsH (~78% identity).…”
mentioning
confidence: 99%
“…Recent studies showed that TcdA uses sulfated glycosaminoglycans as the cell surface attachment factors and LDLR family proteins as the entry receptors. 8 , 12 The primary sequences between Tcnα and TcdA are divergent, with only ~30% identity. In the LCT family, TcdA is most similar to TcsH (~78% identity).…”
mentioning
confidence: 99%
“…Although LRP1 and Megalin can mediate the cellular entry of Tcnα, they were not found in the candidate list of our previous CRISPR screen for Tcnα 13 . Likewise, LRP1 was demonstrated as an entry receptor for TcdA 30 but it did not stand out from the previous genome-wide screen 27 . We noticed that HeLa cells were employed in both genetic screens for TcdA and Tcnα, as well as the following validation experiments.…”
Section: Resultsmentioning
confidence: 83%
“…We noticed that HeLa cells were employed in both genetic screens for TcdA and Tcnα, as well as the following validation experiments. On the other hand, previously Schottelndreier et al used mouse embryonic fibroblasts (MEFs) for studying the role of LRP1 in TcdA entry 30 . According to a public protein profiling database ( http://www.proteinatlas.org ) 31 , 32 , LDLR and LRP1 have contrasting mRNA expression profiles in many different cell lines, while Megalin is absent in most cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the cell surface the two parts remain non-covalently linked. More than 40 distinct ligands have been identified to interact with LRP1 including apolipoproteins and cholesteryl esters in remnants (14, 15), extracellular matrix (ECM) components such as fibronectin (16, 17), a minor-group common cold virus (18) and Rift Valley fever virus (19) as well as bacterial toxins like Clostridium perfringens TpeL (13), Pseudomonas Exotoxin A (ExoA, (20)), TcdA produced by Clostridoides difficile (21) and the vacuolating toxin (VacA) from Helicobacter pylori (22). These diverse ligands do not contain a common binding motif.…”
Section: Introductionmentioning
confidence: 99%